Fostering Participation During Literacy Instruction in Inclusive Classrooms for Students With Complex Support Needs: Educators' Strategies and Perspectives. (May 2021) - Zagona, Alison L.; Lansey, Kirsten R.; Kurth, Jennifer A.; Kuhlemeier, Alena
Existing research has documented evidence-based practices that are effective for supporting students with complex support needs (CSN) to learn academic skills. However, there is a need to learn more about effective instructional strategies for students with CSN during literacy lessons in general education classrooms. In addition, there is a need to understand general education teachers' perspectives on these strategies, including how they learned about them. The purpose of this study was to understand (a) the extent of participation of students with CSN in literacy instruction and activities in general education classrooms, (b) the supports educators provide during these activities, and (c) how educators learned about the strategies they use in their classrooms. We observed nine students with CSN and conducted follow-up interviews with their classroom teachers. Overall, students participated in academic activities for a majority of observations, and these activities addressed a variety of different literacy skills. Educators used research-based instructional practices to support the students including prompts and visual supports. During follow-up interviews, general education teachers described the strategies they used to support students with CSN, and they described how they learned about these strategies. Implications for future research and practice are presented.